1966
DOI: 10.1002/cber.19660991130
|View full text |Cite
|
Sign up to set email alerts
|

Über Ferrocenderivate, VI. Reaktionen von α‐Hydroxy‐alkylferrocenen mit Isocyansäureestern

Abstract: Die Reaktion von u-Hydroxy-alkylferrocenen rnit Aryl-bzw. Aroylkocyanaten fuhrt unter bestimmten Bedingungen nicht ZLI Urethanen, sondern zu sekundaren N-Ferrocenylalkylaminen (la-c, 5a, h) bzw. -amiden (4). Die Amine konnen in Folgereaktionen rnit den Hydroxyalkylferrocenen zu tertiaren N.N-Bis-ferrocenylalkyl-aminen (3 a-c) weiteralkyliert werden. Die analoge Umsetzung von 1.1'-Bis-hydroxymethyl-ferrocen rnit Arylisocyanaten fuhrt zu 1.1'-[2-Ary1-2-aza-trimethylen~-ferrocenen (2-Aryl-2-aza-[3]-ferrocenophane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The synthesis of 2‐aza‐[3]‐ferrocenophane is challenging because of its highly rigid structure. Lorkowski and Kieselack first obtained N ‐aryl‐2‐aza‐[3]‐ferrocenophane from 1,1′‐ferrocenedimethanol with aryl isocyanate in only 6.7 % yield 8a. Plenio reported that N ‐methyl‐2‐aza‐[3]‐ferrocenophane was prepared from [1,1′‐ferrocenediylbis(methylene)]bis(pyridinium) tosylate chloride in 35 % yield 8d.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 2‐aza‐[3]‐ferrocenophane is challenging because of its highly rigid structure. Lorkowski and Kieselack first obtained N ‐aryl‐2‐aza‐[3]‐ferrocenophane from 1,1′‐ferrocenedimethanol with aryl isocyanate in only 6.7 % yield 8a. Plenio reported that N ‐methyl‐2‐aza‐[3]‐ferrocenophane was prepared from [1,1′‐ferrocenediylbis(methylene)]bis(pyridinium) tosylate chloride in 35 % yield 8d.…”
Section: Resultsmentioning
confidence: 99%
“…http://dx.doi.org/10.1016/B978-0-12-800976-5. [4][5][6][7] the examples of the [3]ferrocenophane family (1). 6 This is similar for examples of heteroatom-bridged systems (2 and even 3) (see Scheme 4.1).…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds have been originally synthesised by condensation of 1,1 0 -bis(hydroxymethyl)ferrocene with isocyantes (IV: R = C 6 H 4 X-4, where X = H, OMe, NO 2 [2]), by twofold alkylation of an amine (RNH 2 ) with 1,1 0 -bis(bromomethyl)ferrocene (IV: R = C 6 H 4 NO 2 -4 [3]) or 1,1 0 -bis(N-pyridiummethyl)ferrocene dichloride (IV: R = Me [4]) and, finally, by reductive ammination of ferrocene-1,1 0 -dicarbaldehyde (IV: R = x-[(7-chloro-4-quinolyl)amino]alkyl [5]). More recently, Osakada and co-workers devised a practical synthetic route to ferrocenophanes IV based on Ru-catalysed condensation of 1,1 0 -bis(hydroxymethyl)ferrocene with amines [6].…”
mentioning
confidence: 99%